An unusual case of adrenal cortical carcinoma. Issue 777 (July 1990) - Mufti, G. R.; Farrell, J.
Abstract : We describe a case of non-functioning adrenal cortical carcinoma, which recurred 16 years after surgical adrenalectomy. In addition, the patient was successfully treated for two anatomically separate and histologically different, primary malignant tumours. This case highlights the importance of lifelong follow-up after apparently curative surgical excision of an adrenal tumour.